Sosialisasi Pembuatan Konten Media Sosial dalam Strategi Branding Desa Wisata Sugihmukti - Rachmawati, Indira; Millanyani, Heppy; Sagita, Ardio (Penerbit Widina, Widina Media Utama, 2024)
Sugihmukti Village was inaugurated as a tourist village based on Decree number 556/Kep.770-Disbudpar/2022 issued in 2002. One of the attractions of this village is bird watching activities in collaboration with the